2014
DOI: 10.1063/1.4882027
|View full text |Cite
|
Sign up to set email alerts
|

Modulating resonance behaviors by noise recycling in bistable systems with time delay

Abstract: In this paper, the impact of noise recycling on resonance behaviors is studied theoretically and numerically in a prototypical bistable system with delayed feedback. According to the interior cooperating and interacting activity of noise recycling, a theory has been proposed by reducing the non-Markovian problem into a two-state model, wherein both the master equation and the transition rates depend on not only the current state but also the earlier two states due to the recycling lag and the feedback delay. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It has been reported that time delay may induce the complex dynamics in dynamical systems. [8][9][10][11][12][13][14][15][16][17][18][24][25][26][27][28] In this part, the effect of time delay on bifurcation's behavior has been investigated in system (1) together with Gaussian white noise, as Fig. 4 displays.…”
Section: B Effect Of Time Delay On Bifurcationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that time delay may induce the complex dynamics in dynamical systems. [8][9][10][11][12][13][14][15][16][17][18][24][25][26][27][28] In this part, the effect of time delay on bifurcation's behavior has been investigated in system (1) together with Gaussian white noise, as Fig. 4 displays.…”
Section: B Effect Of Time Delay On Bifurcationmentioning
confidence: 99%
“…Up to now, analytical researches have been concerned with the stability and performance in nonlinear stochastic DDSs, 19 the approximate solutions in nonlinear stochastic systems with small delays, [20][21][22][23] and the dynamical behaviors including resonance and bifurcations. [24][25][26][27][28] Besides, stochastic DDSs are widely used in other fields. For instance, Frank and Beek 29 were dedicated on exploring the biological systems, with the adoption of linear stochastic delay differential equations.…”
Section: Introductionmentioning
confidence: 99%